FAKTOR-FAKTOR PENYEBAB PENYAKIT PERIAPIKAL DAN PULPA PADA LANSIA PUSKESMAS KAGOK SEMARANG - Sariyem Sariyem; Bambang Sutomo; Florida Varianti (Jurnal Kesehatan Gigi, 2018)
TITLETHE CAUSAL FACTORS OF PERIAPICAL AND PULP DISEASE AMONG SENIOR COMMUNITY OF KAGOK COMMUNITY HEALTH CENTER SEMARANGABSTRACTThe high rate of pulp disease and periapical tissue suffered most of the age group of 45-60 years as much as 34% in the elderly group. This study aims to determine the factors causing pulpal disease and periapical tissue in the elderly group at puskesmas Kagok.The sample in this study were 83 elderly people in Wonotingal subdistrict who had a history of cavities. The data were collected by index plaque, salivary hydration, Saliva pH, salivary viscosity and using a questionnaire to know behavior factor, environmental factor, health service factor and heredity factor.The results showed the highest index plaque with bad criterion equal to 57,8%, highest salivary hydration with low criterion equal to 49,3%, highest salivary pH with acid criteria equal to 66,2%, highest salivary viscosity with bad criterion equal to 73,4%. Factors are elderly behavior with medium criterion equal to 66,2%, medium criterion criteria are 63,8%, health service factor with medium criterion equal to 57,8% and descent factor with medium criterion 78,3%. The results of statistical tests show that the relationship between influence and variable variables affected by confusion interval with a value of R 0.303 which indicates the level of low relationship.